Identification of a functional core in the RNA component of RNase MRP of budding yeasts - Li, Xing (Oxford University Press, 2004)
RNase MRP is an endonuclease participating in ribosomal RNA processing. It consists of one RNA and at least nine protein subunits. Using oligonucleotide-directed mutagenesis, we analyzed the functional role of five of the hairpins in the secondary structure of the RNA subunit of Saccharomyces cerevisiae RNase MRP. Deletion of an entire hairpin was either lethal or resulted in very poor growth. However, peripheral portions constituting up to 70% of a hairpin could be deleted without effects on cell growth rate or processing of rRNA. To determine whether these hairpins perform redundant functions, we analyzed mutants combining four or five benign hairpin deletions. Simultaneous removal of four of these hairpin segments had no detectable effect. Removing five created a temperature- and cold-sensitive enzyme, but these deficiencies could be partially overcome by a mutation in one of the RNase MRP protein subunits, or by increasing the copy number of several of the protein subunit genes. These observations suggest that the peripheral elements of the RNA hairpins contain no structures or sequences required for substrate recognition, catalysis or binding of protein subunits. Thus, the functionally essential elements of the RNase MRP RNA appear to be concentrated in the core of the subunit.